Green Household Initiative: Pengenalan Ekonomi Sirkuler dalam Pengelolaan Limbah Rumah Tangga - Dasmaran, Verliani; Permatasari, Novelia Kiki; Sutihat, Eva; Masitoh, Masitoh; Nuraeni, Rini; Al Birun, Muhamad Syehan; Umamah, Neneng; Lestari, Intan (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The increasing generation of household waste in Indonesia, including in Teluklada Village, Sobang District, Pandeglang Regency, poses a serious threat to environmental quality and public health. Low environmental literacy, limited understanding of waste separation, and the prevalence of open burning and mixed waste disposal highlight the urgent need for community-based environmental education. In response to this issue, the Green Household Initiative Community Service Program (PKM) was implemented to enhance public understanding of the circular economy as an alternative approach to household waste management. The methods included field observation, preparation of educational materials, delivery of socialization through presentations and interactive discussions, and basic evaluation of participants’ comprehension. The results indicate a notable improvement in participants’ knowledge of the 3R principles (reduce, reuse, recycle), a positive shift in perceptions regarding the value of waste, and increased awareness of the importance of waste sorting in daily activities. Overall, this program plays a critical role in addressing the urgent need for environmental education and serves as an initial step in strengthening community understanding of circular economy–based waste management.